Hammer Head Hardware Enterprise : Hardware Tools / Fatin Nursyaqirah Kasman ...[et al.] - Kasman, Fatin Nursyaqirah; Nasim, Suhaila; Saharudin, Jazmina; Che Rosmin, Layla Salikin; Wan Izham, Wan Nurul Anahua (2017)
Our main purpose to build this hardware store is to make our hardware store a well-known brand in Johor for a few years later. Which means that, the entire people of Johor will recognize us because of our qualities which include aspect of best price, quality of products and our good hospitality.